1998
DOI: 10.1046/j.1365-2443.1998.00210.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro assembly of the CENP‐B/α‐satellite DNA/core histone complex: CENP‐B causes nucleosome positioning

Abstract: Background: We have studied the nucleosome structure formed from ␣-satellite DNA bound with CENP-B and core histones, in order to develop a previous proposal that the CENP-B dimer may play a critical role in the assembly of higher order structures of the human centromere by juxtaposing CENP-B boxes in long ␣-satellite arrays.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
74
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(85 citation statements)
references
References 75 publications
7
74
0
Order By: Relevance
“…These findings indicate a conserved role for transposable elements in genome organization. Dimerization of CENP-B proteins 42 (this study) bound to LTRs may directly or indirectly promote either local or long-range loops between LTRs of individual Tfs or different Tf elements. As such, enrichment of CENP-B proteins at Tf2 peaks at flanking LTRs but progressively decreases towards the centre of Tf2 elements.…”
Section: Discussionmentioning
confidence: 82%
“…These findings indicate a conserved role for transposable elements in genome organization. Dimerization of CENP-B proteins 42 (this study) bound to LTRs may directly or indirectly promote either local or long-range loops between LTRs of individual Tfs or different Tf elements. As such, enrichment of CENP-B proteins at Tf2 peaks at flanking LTRs but progressively decreases towards the centre of Tf2 elements.…”
Section: Discussionmentioning
confidence: 82%
“…Another possibility could be that the monomer-length conservation could be necessary for the modulation of higher-order structures. The human CENP-B binds to DNA as a dimer; the rigid monomer length may be needed to maintain the appropriate locations of the CENP-B boxes for protein binding (Yoda et al, 1998). It is also possible that the length requirements could be a consequence of the interaction between satellite-array and specialized centromere proteins (Talbert et al, 2004).…”
Section: Changes In Sequence Variabilitymentioning
confidence: 99%
“…Ohzeki et al (2002) report the loss of CENP-B-binding activity when alphoid DNA is modified by point mutations in CENP-B boxes. It has been suggested that the polymorphisms may be involved in the phasing of CENP-B boxes within the satellite, necessary for the formation of higher-order chromatin Satellite DNA in insects T Palomeque and P Lorite structures (Yoda et al, 1998;Choo, 2000). The implication of CENP-B-CENP-B box interaction in the centromereassembly mechanism has been experimentally supported by Ohzeki et al (2002).…”
Section: Changes In Sequence Variabilitymentioning
confidence: 99%
“…CENP-A and CENP-C do not seem to have any obvious sequence specificity in DNA binding. In contrast, CENP-B specifically binds a 17-base pair sequence (the CENP-B box), which appears in every other 171-base pair ␣-satellite repeat in human centromeres (12), and induces nucleosome positioning in the vicinity of the CENP-B box (13). These results suggest that CENP-B may function as a transacting factor, which induces the formation of the centromerespecific heterochromatin.…”
mentioning
confidence: 92%